Single Amino Acid Substitution in the Receptor Binding Domain of Spike Protein Is Sufficient To Convert the Neutralization Profile between Ethiopian and Middle Eastern Isolates of Middle East Respiratory Coronavirus - Sugimoto, Satoko; Kakizaki, Masatoshi; Kawase, Miyuki; Kawachi, Kengo; Ujike, Makoto; Kamitani, Wataru; Sentsui, Hiroshi; Shirato, Kazuya (Microbiology spectrum, 2023)
There have been no reported cases of human Middle East respiratory syndrome (MERS) in Africa, despite the presence of MERS coronavirus (MERS-CoV). Previous studies have shown that recombinant MERS-CoV carrying the S protein of an Ethiopian isolate replicated slower and was more easily neutralized relative to MERS-CoV carrying the S protein of a Middle Eastern isolate. Middle East respiratory syndrome coronavirus (MERS-CoV) is a zoonotic virus that causes MERS, which is endemic in the Middle East. The absence of human cases in Africa despite the presence of MERS-CoV suggests virological differences between MERS-CoVs in Africa and the Middle East. In fact, in the laboratory, recombinant MERS-CoV carrying the spike (S) protein of Ethiopian isolates exhibits attenuated properties, being more easily neutralized and replicating slower than viruses carrying the S protein of Middle Eastern isolate, EMC. In this study, to identify the amino acids that define the different virological features between Ethiopian and Middle Eastern MERS-CoVs, neutralization titers and viral replication were evaluated using recombinant MERS-CoVs carrying amino acid substitution(s) in the S protein. A single amino acid difference introduced into the receptor binding domain was sufficient to reverse the difference in the neutralizing properties of the S protein between Ethiopian and Middle Eastern MERS-CoVs. Furthermore, amino acid mutations in the S1 and S2 regions of S protein were collectively involved in slow viral replication. Since even a single amino acid difference in S protein can reverse the viral properties of MERS-CoV, it should be noted that multiple mutations may induce a significant change. Careful monitoring of genetic alterations in MERS-CoVs in Africa is therefore required to detect the emergence of virulent strains generated by a few genetic differences. IMPORTANCE There have been no reported cases of human Middle East respiratory syndrome (MERS) in Africa, despite the presence of MERS coronavirus (MERS-CoV). Previous studies have shown that recombinant MERS-CoV carrying the S protein of an Ethiopian isolate replicated slower and was more easily neutralized relative to MERS-CoV carrying the S protein of a Middle Eastern isolate. In this study, we investigated the amino acid(s) in S protein associated with the different viral characteristics between Ethiopian and Middle Eastern MERS-CoVs. The results revealed that a single amino acid difference in the receptor binding domain was sufficient to reverse the neutralization profile. This implies that slight genetic changes can alter the predominant population of MERS-CoV, similar to the transition of variants of severe acute respiratory syndrome coronavirus-2. Careful genetic monitoring of isolates is important to detect the spread of possible virulent MERS-CoVs generated by mutation(s).